Essential Basic Structural Components in the Educational Process of a Medical University: Komponen Struktural Dasar yang Penting dalam Proses Pendidikan di Universitas Kedokteran - Toyirovna, Yuldashova Shakhlo (Academia Open, 2025)
General Background: The evolving demands of global healthcare systems require medical education to shift from traditional theoretical instruction to innovative, competency-based learning. Specific Background: In Uzbekistan, this transformation is aligned with national reforms emphasizing the development of independently thinking medical professionals. Knowledge Gap: While creativity is acknowledged as vital in medical training, there remains a lack of comprehensive models explaining how integrative-creative thinking is systematically embedded within pedagogical structures, especially in post-Soviet contexts. Aims: This study aims to identify the essential structural components of integrative-creative pedagogy in Uzbekistan’s medical universities, using Bukhara State Medical Institute as a case. Results: The findings reveal a procedural model integrating motivational-personal engagement, intuitive insight, imaginative reasoning, and clinical improvisation, contributing to creative-professional identity formation. Novelty: The research proposes a contextualized framework where creativity is continuous, emerging from structured educational-cognitive practices, rather than episodic. Implications: These insights offer practical guidance for curriculum designers and educators aiming to foster adaptive, innovative clinicians, and inform global conversations on pedagogical transformation in medical education. Highlight : Identifies creative thinking as a structural necessity in medical training. Emphasizes the role of student-led inquiry and clinical simulations in fostering professional identity. Proposes a localized pedagogical model suitable for medical education reform in Uzbekistan. Keywords : Creative Thinking, Integrative Learning, Medical Education, Pedagogical Innovation, Clinical